2008
DOI: 10.1139/b08-064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temporal heterogeneity of watering on size of an annual forb, Perilla frutescens (Lamiaceae), depend on soil nutrient levels

Abstract: Temporal heterogeneity of watering affects plant growth. When the same total amount of water is supplied, frequent watering leads to greater plant size than infrequent watering. However, the effects of a given watering regime can differ when nutrient levels vary. An experiment was designed to test the hypothesis that the effects of temporal heterogeneity of watering on plant growth also vary as a function of nutrient levels. Perilla frutescens (L.) Britton was grown using different combinations of nutrient lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Water heterogeneity and nutrient level both affected pot yield independently, although in a previous study, the homogeneous water supply increased the biomass of individual P. frutescens plants, especially at a high nutrient level (Hagiwara et al 2008). Plants under nutrient-rich conditions are expected to grow larger and to be more sensitive to variability in soil moisture than those under nutrient-poor conditions because of their large demands for water (Stevens et al 2006).…”
Section: Pot Yield and Individual Biomassmentioning
confidence: 94%
See 3 more Smart Citations
“…Water heterogeneity and nutrient level both affected pot yield independently, although in a previous study, the homogeneous water supply increased the biomass of individual P. frutescens plants, especially at a high nutrient level (Hagiwara et al 2008). Plants under nutrient-rich conditions are expected to grow larger and to be more sensitive to variability in soil moisture than those under nutrient-poor conditions because of their large demands for water (Stevens et al 2006).…”
Section: Pot Yield and Individual Biomassmentioning
confidence: 94%
“…Under natural conditions, it grows on the forest floor under canopy gaps in evergreen forests in Japan, reaching heights of 50-80 cm, and flowers from September to October (Iwatsuki et al 1993). Previous studies showed that P. frutescens responded to water heterogeneity, and that it can be a good model species for studies of responses to watering regimes (Hagiwara et al 2008(Hagiwara et al , 2010. Seeds of P. frutescens were obtained from the Atariya Seed Co. (Chiba, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutrient levels must be considered in the study of water heterogeneity for three reasons: (1) nutrient availability depends on water availability (Lambers et al 1998); (2) plants will be more sensitive to variability in water supply under nutrientrich than under nutrient-poor conditions, because they grow larger and require more water when nutrients are abundant (Goldberg and Novoplansky 1997;Stevens et al 2006); and (3) nutrient levels affect the root growth of plants (Fitter 1997), and this consequently can affect water uptake. In fact, an interactive effect of water heterogeneity and nutrient levels has been reported in the annual herbaceous species Perilla frutescens L. (Hagiwara et al 2008(Hagiwara et al , 2010. A few agricultural studies have also showed the interaction of water heterogeneity and nutrient levels (Silber et al 2003;Xu et al 2004).…”
Section: Introductionmentioning
confidence: 98%